2022
DOI: 10.7759/cureus.28630
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 Vaccination on Menstrual Cycle: A Cross-Sectional Study From Karachi, Pakistan

Abstract: BackgroundThe coronavirus disease 2019 (COVID-19) disease triggered a worldwide health catastrophe. To deal with this deadly situation multiple vaccines were developed and a mass immunization program started globally. However, vaccine hesitancy was seen, especially among women of reproductive age, having concerns that the vaccine might affect their menstrual cycle. This study investigated the link between COVID-19 vaccination and menstrual abnormalities. It is essential for us to understand the effects of vacc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0
13

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 23 publications
2
3
0
13
Order By: Relevance
“…Focusing on the menstrual bleeding disturbances, those related with the length and flow stand out. This observation is consistent with that found in previous studies reporting longer-lasting menstruation [14,20], and/or heavier flow [14,21,25,33,34] than usual in vaccinated women. Unexpectedly, increased bleeding has also been observed in women using hormonal contraception [14,21,25,33], which may indicate that certain immunological processes may be also involved.…”
Section: Discussionsupporting
confidence: 93%
“…Focusing on the menstrual bleeding disturbances, those related with the length and flow stand out. This observation is consistent with that found in previous studies reporting longer-lasting menstruation [14,20], and/or heavier flow [14,21,25,33,34] than usual in vaccinated women. Unexpectedly, increased bleeding has also been observed in women using hormonal contraception [14,21,25,33], which may indicate that certain immunological processes may be also involved.…”
Section: Discussionsupporting
confidence: 93%
“…Another retrospective online study involving females aged 18 to 41 years also reported that 20.8% of participants experienced delayed menstruation and 21.4% experienced early menstruation, findings that mirror our own study [19]. Similarly, a study among Pakistani women aged 18 and above reported that one-tenth of the participants missed their menstrual cycle post-SARS-CoV-2 vaccination, further supporting our findings [21]. Our study also aligns with the findings of the Arizona COVID-19 cohort (CoVHORT), which also documented irregularities in the menstrual cycle in 43% of the participants [22].…”
Section: Discussionsupporting
confidence: 89%
“…Consistent with the previous research ndings, the results of this study also presented evidence that changes to the women's menstrual cycle after exposure to the Covid-19 vaccination are short lived. 9,28,29,30 The results of the chi-square test analysis indicated that there were fewer incidences of menstrual disturbances after the second dose cycle compared to the menstrual abnormalities after the rst dose cycle. The implication is that the extent of immunological stimulation of the menstrual cycle hormones tends to decrease after the second dose cycle.…”
Section: Discussion Of Findingsmentioning
confidence: 99%